Analyze of production performance of vaname shrimp Litopenaeus vannamei culture and water quality on earthen pond and HDPE-lined pond - Zulfana Fikru Sifa; Kukuh Nirmala; Yuni Puji Hastuti; Eddy Supriyono (Indonesian Society of Scientific Aquaculture (ISSA), 2026)
Litopenaeus vannamei is a leading aquaculture commodity with high economic value. Efforts to enhance the production of L. vannamei shrimp can be achieved by selecting the type of pond. Culture ponds are crucial in controlling water quality and managing culture waste. Based on these conditions, selecting the appropriate type of pond is essential to improve the production performance of L. vannamei shrimp. This study aimed to analyze the effects of earthen ponds and high density polyethylene (HDPE)-lined ponds on production performance and water quality factors, identify key water quality parameters influencing shrimp yield, and conduct an economic analysis. This study was conducted with two types of ponds, earthen ponds and HDPE-lined ponds. Water quality factors were analyzed weekly using a composite sampling method. Meanwhile, shrimp weight sampling was conducted weekly after 35 days of culture using 30 shrimp for each pond. The results showed that shrimp production performance in HDPE-lined ponds was significantly higher than in earthen ponds. This enhanced production performance was attributed to the more optimal water quality parameters in HDPE-lined ponds, particularly the lower abundance of Cyanophyta. Furthermore, the soil quality in earthen ponds also reduces shrimp survival rates, leading to decreased pond productivity. Although the production costs for HDPE-lined ponds were 17.54% higher than earthen ponds, this investment increases farmers' total revenue by 57.20%. HDPE ponds produce high production performance and healthier water quality, thereby increasing farmers' income and proving economically viable. Keywords: economic, growth, pond type, soil Abstrak Litopenaeus vannamei merupakan salah satu komoditas unggulan perikanan budidaya yang memiliki nilai ekonomis tinggi. Upaya untuk meningkatkan produksi udang L. vannamei dapat dilakukan dengan memilih jenis tambak. Tambak budidaya sangat penting dalam mengontrol kualitas air dan mengelola limbah budidaya. Berdasarkan kondisi tersebut, pemilihan jenis tambak yang tepat sangat penting untuk meningkatkan performa produksi udang L. vannamei. Penelitian ini bertujuan untuk menganalisis pengaruh tambak tanah dan tambak berlapis high density polyethylene (HDPE) terhadap kinerja produksi dan faktor kualitas air, mengidentifikasi parameter kualitas air utama yang mempengaruhi hasil panen udang, dan melakukan analisis ekonomi. Penelitian ini dilakukan dengan dua jenis tambak, yaitu tambak tanah dan tambak berlapis HDPE. Faktor kualitas air dianalisis setiap minggu dengan menggunakan metode pengambilan sampel komposit. Sementara itu, pengambilan sampel berat udang dilakukan setiap minggu setelah 35 hari budidaya dengan menggunakan 30 ekor udang untuk setiap tambak. Hasil penelitian menunjukkan bahwa kinerja produksi udang ditambak HDPE lebih tinggi dibandingkan tambak tanah. Tingginya kinerja produksi udang ini dikarenakan tambak HDPE memiliki parameter kualitas air yang lebih optimal dibandingkan dengan tambak tanah, terutama pada kelimpahan Cyanophyta yang lebih rendah. Selain itu, kualitas tanah di tambak tanah juga menurunkan tingkat kelangsungan hidup udang sehingga mengakibatkan rendahnya produktivitas tambak tanah. Meskipun biaya produksi untuk tambak yang dilapisi HDPE 17.54% lebih tinggi dibandingkan tambak tanah, namun biaya investasi ini dapat meningkatkan total pendapatan petambak sebesar 57.20%. Tambak HDPE menghasilkan kinerja produksi yang tinggi dan kualitas air yang lebih optimal, sehingga meningkatkan pendapatan petani dan terbukti layak secara ekonomi. Kata kunci: ekonomi, pertumbuhan, tanah, tipe tambak